THE EFFECTİVENESS OF JİGSAW READİNG AS A COOPERATİVE LEARNİNG STRATEGY İN EFL CLASSROOMS (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2026)
Jigsaw reading is a cooperative learning strategy that promotes active learner engagement, responsibility, and collaboration in reading lessons. This article examines the theoretical foundations, instructional procedures, and pedagogical benefits of jigsaw reading in English as a Foreign Language (EFL) classrooms. Drawing on previous research and classroom-based evidence, the study highlights how jigsaw reading enhances reading comprehension, learner autonomy, and communicative competence. The findings suggest that jigsaw reading is an effective student-centered approach that supports both cognitive and social development in language learning contexts.